Implementasi Bantuan Militer Kepada Pemerintah Daerah Menurut UU Nomor 7 Tahun 2012 - Winarna, Agus; Prasetyo, Teguh; Sutrisno, Sutrisno (Penerbit Goodwood, 2025)
Purpose: The government bears the primary responsibility for national security and public welfare, including resolving regional security issues. One of the state’s strategic functions involves handling social conflicts through coordinated military assistance to local governments, as regulated under Law Number 7 of 2012. This study addresses two main issues: first, the implementation of military assistance to regional governments in handling social conflicts based on dignified justice as part of Military Operations Other than War (MOOTW) under operational control; second, the legal liability associated with social conflict management. Methodology/approach: This research uses a normative juridical approach, supported by interviews, statutory regulations, and relevant legal documents. The study examines how the law regulates military roles in civil conflict management and evaluates their implementation through doctrinal and empirical analysis. Results/findings: Findings reveal that the government’s legal policy emphasizes the importance of legal awareness and obedience as foundations for national stability. The support of law enforcement institutions and the military's role reflects a broader legal-political commitment to uphold the rule of law during conflict resolution. Conclusions: TNI soldiers play a crucial role as both combatants and community agents in delivering military assistance to regional governments. Their coordination with the police and civil institutions promotes synergy and effective conflict handling rooted in dignified law enforcement. Limitations: The study is limited to the application of Law No. 7 of 2012 and does not cover broader sociopolitical dynamics of conflict. Contribution: This study reinforces the importance of military assistance in regional governance, promoting integrated defense strategies that support dignified and lawful conflict resolution.